4/x-6/2x-1=1/2x

Simple and best practice solution for 4/x-6/2x-1=1/2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4/x-6/2x-1=1/2x equation:



4/x-6/2x-1=1/2x
We move all terms to the left:
4/x-6/2x-1-(1/2x)=0
Domain of the equation: x!=0
x∈R
Domain of the equation: 2x!=0
x!=0/2
x!=0
x∈R
Domain of the equation: 2x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
4/x-6/2x-(+1/2x)-1=0
We get rid of parentheses
4/x-6/2x-1/2x-1=0
We calculate fractions
8x/2x^2+(-1x-6)/2x^2-1=0
We multiply all the terms by the denominator
8x+(-1x-6)-1*2x^2=0
Wy multiply elements
-2x^2+8x+(-1x-6)=0
We get rid of parentheses
-2x^2+8x-1x-6=0
We add all the numbers together, and all the variables
-2x^2+7x-6=0
a = -2; b = 7; c = -6;
Δ = b2-4ac
Δ = 72-4·(-2)·(-6)
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1}=1$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(7)-1}{2*-2}=\frac{-8}{-4} =+2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(7)+1}{2*-2}=\frac{-6}{-4} =1+1/2 $

See similar equations:

| 14+8x=62 | | 3=2h-9 | | 9y-15y+12-6y=0 | | 3s=-24+9s | | 0=n+17 | | 2y/3-23=55 | | -3m+5m=-4 | | 11-8z=-10z-5 | | 19c-9c=10 | | 0=-16t2+10t+6 | | 2x+1-(-1x+-2)=2-(-2x) | | 55=8n+9 | | 9y+15y+12-6y=0 | | 5m-4=35 | | (10^x+10^-x)/2=20 | | 4p+5=26 | | -13+4x=6(5x+2)-x | | -8u=-27+u | | -1(c+1)=-3 | | 2x+9/3=7 | | 2t^2-7t-1=0 | | -7b-90=2b | | 5x/3-30=3 | | -6+n/4=-5 | | 2(s-2)+2=8 | | 4/x+3)-(3/x-3)=7/3 | | -x^2+8x-11=x-1 | | 4+5y+2y=-38 | | -9n-5=13 | | x+3(x*1/3)=25 | | 16−3p=​3​2p+5 | | 5r-4=3r-18 |

Equations solver categories